EFFECT OF ORGANIC MANURE ON GERMINATION AND EARLY GROWTH STAGES OF MAIZE (Zea mays L.) GROWN ON OIL POLLUTED SOIL - Nayaya, J. A.; Shuaibu, Y. M.; Abdu, A. I.; Bala, R. A.; Kawure, S.; Abdulkadir S. U. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was carried out to investigate the effect of organic manure on germination and early growth stages of maize grown on oil polluted soil at the Agronomy Laboratory of the Faculty of Agriculture and Agricultural Technology, Abubakar Tafawa Balewa University Bauchi. The treatment consisted of poultry manure, cow dung, poultry manure + engine oil, poultry manure + premium motor spirit, cow dung + engine oil, cow dung + premium motor spirit and a control. These were arranged in completely randomized design (CRD) repeated three times. The soils were collected from an arable field, air-dried and artificially contaminated with engine oil and premium motor spirit to simulate an oil spill scenario. Cow dung, and poultry manure ware used as source of organic manure. Data were collected on plant height, number of leaves, stem girth and leaf area. All data collected were subjected to Analysis of variance (ANOVA) and means were separated using Duncan’s multiple range test. The result shows a significant (P<0.05) difference in plant height on various soils polluted with oil in week 1 and no significant difference was observed in week 2 and week 3. The soil polluted with engine oil (EO) and soil with cow dung (CD) had the tallest plants (42.3 and 41.1) in week 1, followed by control, polluted soil with engine oil plus cow dung (EO+CD) as remediation and premium motor spirit (PMS). On number of leaves, there’s no significant difference (P<0.05) in week 2 and week 3 while significant difference (P<0.05) was observed in week 1. Control has the highest number of leaves (4.0) followed by CD, EO+CD, EO+PM and PMS which are 3.33, 3.33, 3.33 and 3.67 respectively. Leaf area on the other hand, a significant difference (P<0.05) on oil polluted soils remediated with cow dung and poultry manure in week I and week 2 with no significant difference (P<0.05) in week 3. On stem girth however, the result shows no significant difference (P<0.05) between all the treatments in week 2 and 3. However significant difference (P<0.05) was observed in week 1. It can be concluded that, oil polluted soils have effect on early growth stages of maize plant and organic manure can be used to reduce the effect of oil polluted soil. Based on the result of this study, oil polluted soil should not be used for maize production even if remediated with organic manure and Further research is recommended on the use of combination of organic manures and inorganic fertilizer.